2023
DOI: 10.1002/mdc3.13810
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Subcutaneous Infusion Delivery of Apomorphine in Parkinson's Disease: A Systematic Review

Abstract: BackgroundContinuous subcutaneous apomorphine infusion (CSAI) is one of the advanced therapies for Parkinson's disease (PD).MethodsA systematic review of all published articles in English on CSAI for PD till January 30, 2022 was conducted.ResultsA total of 82 articles met the search criteria. Publications included retrospective or prospective open‐label observational studies, with a limited number of randomized control trials (RCT). Publications were highly heterogeneous and focused on different aspects of CSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
(207 reference statements)
0
4
0
Order By: Relevance
“…Multiple open‐label studies confirm the efficacy of CAI in the reduction of daily off‐time. 40 , 41 , 42 , 43 Despite several retrospective large case series, detailed long‐term effects are understudied and have been reviewed recently 43 ; however, retrospective data confirm a sustained reduction in motor fluctuations for at least 2 years. 44 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple open‐label studies confirm the efficacy of CAI in the reduction of daily off‐time. 40 , 41 , 42 , 43 Despite several retrospective large case series, detailed long‐term effects are understudied and have been reviewed recently 43 ; however, retrospective data confirm a sustained reduction in motor fluctuations for at least 2 years. 44 …”
Section: Resultsmentioning
confidence: 99%
“…Multiple open-label studies confirm the efficacy of CAI in the reduction of daily off-time. [40][41][42][43] Despite several retrospective large case series, detailed long-term effects are understudied and have been reviewed recently 43 ; however, retrospective data confirm a sustained reduction in motor fluctuations for at least 2 years. 44 Although effectiveness and safety of unilateral radiofrequency pallidotomy could be shown in EBM reviews for fluctuating PD patients, the GL recommends this only if other treatment options are not available.…”
Section: The Severely Fluctuating Patientmentioning
confidence: 99%
“…Particularly, sleep quality has shown enhancement in multiple studies, attributed partly to a positive influence on concomitant Restless Legs Syndrome. Furthermore, a positive impact on apathy and depression has been documented, along with a reduction in nocturia (Todorova and Chaudhuri 2013;Meira et al 2021;Kukkle et al 2023).…”
Section: Continuous Application Of Subcutaneous Apomorphine (Csai)mentioning
confidence: 99%
“… 7 Finally, recent reviews confirmed all these results: improvement in OFF-time duration and in various non-motor symptoms (including neuropsychiatric disorders) following CSAI, as well as its safety and efficacy in people with advanced Parkinson’s disease. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%